Accounting for One-off Operations when Assessing Underlying Fiscal Positions - Joumard, Isabelle (OECD Economics Department Working Papers, 2008)
Frequent recourse to large one-off operations in a number of OECD countries has undermined the accuracy of cyclically adjusted fiscal balances as a measure of both the sustainability of public finance and the fiscal stance. This paper first provides detailed information on the nature and amount of these one-offs for 9 OECD countries. The paper then presents a new indicator - the "underlying" fiscal balance - which effectively eliminates the impact of one-offs and cyclical developments. One-offs are derived as the deviations from trend in net capital transfers, i.e. from widely available national account data. This approach provides a consistent treatment of one-offs both across countries and over time, avoiding the potential information biases which could result from an individual identification of one-offs